Proposal of a model of teaching and learning history in Teacher Training based on object teaching - N. Llonch Molina (Universitat Politècnica de València, 2017)
This work shows an experiment in the teaching of History in teacher-training programs based on discovery learning from primary sources, being the object teaching and the inductive method learning and experiencing the main axis of the project, which was carried out along two courses and involved 327 students. The main objective was to develop a teaching-learning method applied to History for future teachers of Primary Education and provide them with alternative teaching methodologies at school. In order to evaluate this experience both from the results obtained and from the perspective of the students' perception, the results of the assessment rubrics for the two main activities are shown on the one hand, and on the other, the students' voices were collected through closed questionnaires, anonymous opinion reports, sections of some projects and commentaries extracted from the blog Espai Híbrid. The experiment and the results obtained support the work both for the marks achieved and because the students involved acknowledged having experienced a different way to approach History; much more satisfactory in terms of learning and enjoyment of the subject. Besides, they expressed their will to implement similar methodologies in their future careers. We conclude that the proposal of a learning-teaching model for History, with its corresponding adaptations, is useful and applicable at different educational levels.